Comparison of Two Respiratory Support Strategies for Stabilization of Very Preterm Infants at Birth: A Matched-Pairs Analysis - Martherus, Tessa; Oberthuer, André; Dekker, Janneke; Kirchgaessner, Christoph; van Geloven, Nan; Hooper, Stuart B.; Kribs, Angela; te Pas, Arjan B. (Frontiers in Pediatrics, 2019)
Objective Respiratory support for stabilizing very preterm infants at birth varies between centres. We retrospectively compared two strategies that involved either increasing continuous positive airway pressures (CPAP) or increasing oxygen supplementation. Methods Matched-pairs of infants (<28 weeks of gestation) were born at either Leiden University Medical Center (low-pressure: CPAP 5-8 cmH2O and/or positive pressure ventilation (PPV) and fraction of inspired oxygen (FiO2) 0.3-1.0; n=27) or University Hospital of Cologne (high-pressure: CPAP 12-35 cmH2O, no PPV and FiO2 0.3-0.4; n=27). Respiratory support was initiated non-invasively by facemask at both units. Infants (n=54) were matched between centres for gestational age and birth weight to compare physiological and short-term clinical outcomes. Results In the low-pressure group, 20/27 (74%) infants received 1-2 sustained inflations (20, 25 cm H2O) and 22/27 (81%) received PPV (1:19-3:01 minutes) using pressures of 25-27 cm H2O. Within 3 minutes of birth (median (IQR)), mean airway pressures (12 (6-15) vs 19 (16-23) cmH2O, p<0.001) and FiO2 (0.30 (0.28-0.31) vs 0.22 (0.21-0.30), p<0.001) were different in low- vs high-pressure groups, respectively. SpO2 and heart rates were similar. After 3 minutes, higher FiO2 levels (0.62 (0.35-0.98) vs 0.28 (0.22-0.38), p=0.005) produced higher SpO2 levels (77 (50-92) vs 53 (42-69)%, p<0.001) in the low-pressure group, but SpO2/FiO2 and heart rates were similar. While intubation rates during admission were significantly different (70% vs 30%, p=0.013), pneumothorax rates (4% vs 19%, p=0.125) and occurrence of spontaneous intestinal perforations (0% vs 15%, p=0.125) were similar between groups. Conclusion Infants (<28 weeks) can be supported non-invasively at birth with either higher or lower pressures and while higher pressure support may require less oxygen, it does not eliminate the need for oxygen supplementation. Future studies have to examine the effect of high pressures and pressure titration in the delivery room.